Analisis Sistem Drainase Jalan Raya Porong Berbasis Zero Run-Off Di Kabupaten Sidoarjo - Sultonulazkar, Aulia; Andawayanti, Ussy; Sumiadi, Sumiadi (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2022)
Floods occur annually at the Sidoarjo Mud Area and the surroundings, especially at the Porong Highway, Sidoarjo Regency, East Java. The mudflow could cause several problems on the drainage system. Therefore, the inundation needs to be handled with an alternative drainage system which is environmentally friendly, such as Zero Run-Off. The analysis of hydrological data was performed at the Porong Rain Station to identify the discharge design of the drainage channel. From the results of Â hydrological analysis using a 5-year return period at the West Ketapang Drainage Subsystem design, it was shown that the lowest value of the flood discharge was 0.527 m3/s and the largest value was 3.199 m3/s. The results of the evaluation showed that 6 of the 9 existing channels required an inundation. The selected interventions were to build the infiltration channels, channel rehabilitation and rehabilitation of pump. The inundation discharge was reduced by 33.15% after conducting the intervention. Therefore, further intervention such as channel rehabilitation and pump system rehabilitation was maintained until the total inundation discharge was reduced by 100%. Furthermore, the total cost budget plan for each project was IDR 13,018,111,886.Kawasan Lumpur Sidoarjo kerap terjadi banjir tahunan pada daerah sekitarnya, khususnya Jalan Raya Porong, Kabupaten Sidoarjo. Semburan lumpur yang masih terjadi menyebabkan permasalahan pada sistem drainase, sehingga genangan perlu ditangani dengan alternatif drainase berwawasan lingkungan berbasis Zero Run-Off. Data Stasiun Hujan Porong digunakan untuk pengolahan data hidrologi guna mengetahui debit rancangan pada saluran drainase. Dari hasil analisa hidrologi memakai kala ulang 5 tahun, didapatkan nilai debit banjir rancangan Subsistem Drainase Ketapang Barat dengan nilai terkecil 0,527 m3/dt dan terbesar 3,199 m3/dt. Hasil evaluasi didapatkan 6 dari 9 saluran yang ada perlu dilakukan penanganan genangan. Upaya penanganan yang dipilih yaitu dengan membuat saluran resapan, rehabilitasi saluran dan rehabilitasi sistem pompa kolam detensi. Setelah dilakukan upaya penanganan dengan alternatif saluran resapan, debit genangan yang tereduksi sebesar 33,15%. Maka dari itu dilanjutkan penanganan lanjutan dengan rehabilitasi saluran dan rehabilitasi sistem pompa, total debit genangan yang tereduksi 100%. Selanjutnya dilakukan perhitungan rencana anggaran biaya total pada masing â€“ masing pengerjaan, didapatkan total anggaran sebesar Rp. 13.018.111.886.